Functional analysis of CYP71AV1 reveals the evolutionary landscape of artemisinin biosynthesis - Chen, Fang-Yan; Mu, Qiu-Yan; Xu, Bing-Yi; Lei, Yu-Chen; Liu, Hui-Ying; Fang, Xin (Frontiers in Plant Science, 2024)
Artemisinin biosynthesis, unique to Artemisia annua, is suggested to have evolved from ancestral costunolide biosynthetic pathway commonly found in the Asteraceae family. However, the evolutionary landscape of this process is not fully understanded. The first oxidase in artemisinin biosynthesis, CYP71AV1, also known as amorpha-4,11-diene oxidase (AMO), has specialized from ancestral germacrene A oxidases (GAOs). Unlike GAO, which exhibits catalytic promiscuity towards amorpha-4,11-diene, the natural substrate of AMO, AMO has lost its ancestral activity on germacrene A. Previous studies have suggested that the loss of GAO copy in A. annua is responsible for the abolishment of costunolide pathway. In the genome of A. annua, there are two copies of AMO, each of which has been reported to be responsible for the different product profiles of high-and lowartemisinin production chemotypes. Through analysis of their tissue-specific expression and comparison of their sequence with other GAOs, we have discovered that one copy of AMO (AMOHAP) exhibits a different transcript compared to the reported artemisinin biosynthetic genes and shows more sequence similarity to other GAOs in the catalytic regions. Furthermore, in our subsequent in vitro enzymatic assay, the recombinant protein of AMOHAP unequivocally demonstrated germacrene A oxidase activity. This result clearly indicates that AMOHAP is a GAO rather than an AMO, and that its promiscuous activity on amorpha-4,11-diene has led to its misidentification as an AMO in previous studies. In addition, the divergent expression pattern of AMOHAP compared to that of upstream germacrene A synthase may have contributed to the abolishment of costunolide biosynthesis in A. annua. Our findings reveal a complex evolutionary landscape in which the emergence of a new metabolic pathway replaces an ancestral one.